First farmers of the Carpathian Basin : changing patterns in subsistence, ritual and monumental figurines - Bánffy, Eszter (2019)
This study explores and demonstrates processes of cultural change in the first half of the 6th millennium cal BC, among the Koeroes and Starcevo groups of the northern marginal zones of the Balkans. Within this period and zone, which forms the southern part of the Carpathian basin, clay was the fundamental and most abundant building block of material culture, architecture, everyday life and cult practices. Clay walls, furniture, ten thousands of vessels, hundreds of clay figurines and other cult objects accumulated as huge piles of clay debris in every settlement. Traditional system of subsistence patterns ceased to fully function when these first farmers occupied cool and wet hilly forested landscapes: the environmental and cognitive challenges gradually led to the decline of this clay-centred orbit. At the same time, these changes gave birth to a no-less stunning world constructed more of timber and stones, with transformations in subsistence, material culture and rituals. This transition is inextricably bound up with the formation of the first farmers' communities of Central Europe, the Bandkeramik (LBK)